Step 1: Combine like terms to get:
5 − 12 − 6 = -10 + 7 − 1
Step 2: Get the x-terms on the same side of the equation:
5 − 12 − 6 = -10 + 6
Step 3: Get the constants on the same side of the equation:
-13 = -4
Step 4: Use Division Property of Equality:
-13 ÷ -4 = 1
Answer: x = 1
Fill in the blanks to follow the steps in solving the equation: %0D%0A5%0D%0A%0D%0A−%0D%0A12%0D%0A−%0D%0A6%0D%0A%0D%0A=%0D%0A−%0D%0A10%0D%0A%0D%0A+%0D%0A7%0D%0A−%0D%0A1%0D%0A%0D%0AStep 1: Combine like terms to get: Response area%0D%0A%0D%0AStep 2: Get the x-terms on the same side of the equation: Response area%0D%0A%0D%0AStep 3: Get the constants on the same side of the equation: Response area%0D%0A%0D%0AStep 4: Use Division Property of Equality: Response area
1 answer